Penerapan E-Commerce Ditinjau dari Analisa Peluang Pasar dengan Menggunakan Framing Market Opportunity Method - Utama, Ditdit N. (JIK: Jurnal Ilmu Komputer, 2003)
E-commerce implementation is not talking about Technical ability only, but talking about technology aspect, human resource aspect, social aspect and outside company opportunity aspect too. In this journal, it will be explained about how to frame market opportunity and it’s implemented in to right e-commerce technology.Kata Kunci: E-Commerce, market opportunity